Increased Autophagy of Rice Can Increase Yield and Nitrogen Use Efficiency (NUE) - Yu, Jinlei; Zhen, Xiaoxi; Li, Xin; Li, Nan; Xu, Fan (Frontiers in Plant Science, 2019)
Autophagy (self-eating), a conserved pathway in eukaryotes, which is designed to handle cytoplasmic material in bulk and plays an important role in the remobilization of nutrient, such as nitrogen (N) under suboptimal nutrient conditions. Here, we identified a core component of an autophagy gene in rice (Oryza sativa), OsATG8a, with increased expression levels under N starvation conditions. Overexpression of OsATG8a significantly enhanced the level of autophagy and the number of effective tillers in the transgenic rice. In addition, the transgenic lines accumulated more N in grains than in the dry remains and the yield was significantly increased under normal N conditions. Further N allocation studies revealed that the nitrogen uptake efficiency (NUpE) and nitrogen use efficiency (NUE) significantly increased. Otherwise, under suboptimal N conditions, overexpression of OsATG8a did not seem to have any effect on yield and NUE, but NUpE was still improved significantly. Based on our findings, we consider OsATG8a to be a great candidate gene to increase NUE and yield.